Introduction to the modelling of marine ecosystems - Fennel, W. (Elsevier oceanography series ;, 2004)
Modelling of marine ecosystems is a rapidly developing branch of interdisciplinary oceanographic research. Introduction to the Modelling of Marine Ecosystems is the first consistent and comprehensive introduction to the development of models of marine ecosystems. It begins with simple first steps of modelling and develops more and more complex models. This step-by-step approach to increasing the complexity of the models is intended to allow students of biological oceanography and interested scientists with only limited experience in mathematical modelling to explore the theoretical framework and familiarize oneself with the methods. The book describes how biological model components can be integrated into three dimensional circulation models and how such models can be used for 'numerical experiments'. The book illustrates the mathematical aspects of modelling and gives application examples. The tutorial aspect of the book is supported by a set of MATLAB programs, which are provided on an accompanying CD-Rom and which can be used to reproduce many of the results presented in the book. Also available in paperback, ISBN 0-444-51704-9.